A high wet ground performance tread rubber composition

CN122878645APending Publication Date: 2026-10-09KUMHO TIRE (TIANJIN) CO INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611172911.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,该技术方案在提升轮胎湿地抓地性能方面效果有限,难以满足不断提高的安全性能需求

Benefits of technology

(1)本发明采用的氢化石油树脂(尤其是C9加氢石油树脂及C5/C9共聚加氢树脂)自身含有苯乙烯、甲基苯乙烯、茚、甲基茚等刚性基团,玻璃化转变温度(Tg)较高(20-60℃)。与橡胶基体共混后,可通过分子链的物理缠结提升胶料整体Tg,使胶料在0℃附近处于粘弹态区间,在此温度下材料展现出优异的能量耗散能力,与轮胎的湿地抓着性能密切相关。在动态应变下,橡胶分子链段运动调整速度跟不上应变频率,从而增大滞后损失,使0℃区间损耗因子(tanδ@0℃)显著提升。动态力学性能测试结果表明,实施例1-3组的tanδ@0℃较对比例组(0.466)分别提高了31.3%、15.9%和7.9%,湿地抓地指数(以对比例为100%基准)分别提升至131%、116%和108%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The application discloses a kind of high wetland performance's tread rubber composition, belongs to tire manufacturing technical field.It includes following weight parts raw materials: base rubber 100 parts, hydrogenated petroleum resin 10-30 parts, silane coupling agent 10 parts, reinforcing agent 105 parts, antioxidant 6 parts, active agent 5 parts, softener 0-15 parts, vulcanizing agent 1 part, accelerator 2.5 parts and adjuvant 5 parts.The application replaces part of environmental protection aromatic hydrocarbon oil by using hydrogenated petroleum resin, utilizes its high glass transition temperature and good compatibility with rubber, so that the loss factor of compound 0 DEG C is significantly improved, thereby enhancing the energy dissipation capacity and adhesion of tire on wet road surface.Meanwhile, the saturated molecular structure of hydrogenated petroleum resin can inhibit hysteresis loss, and the controllable adjustment of wetland braking performance and rolling resistance is realized, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of tire manufacturing technology, and more specifically to a tread rubber composition with high wet performance. Background Technology

[0002] With the rapid development of the automotive industry, the driving safety of electric vehicles (EVs) on wet and slippery roads has received increasing attention from the industry. In particular, the Automatic Emergency Braking (AEB) system equipped in new energy vehicles places more stringent technical requirements on the braking performance of tires on wet roads. The braking ability of tires on wet and slippery roads directly affects the braking, steering, and high-speed driving stability of vehicles in rainy or slippery conditions, and is one of the key factors determining the overall safety performance of a vehicle.

[0003] Currently, the tire industry commonly employs a composite technology involving the addition of silica and solution styrene-butadiene rubber (SSBR) to improve tire braking performance and reduce rolling resistance. However, this approach has limited effectiveness in enhancing wet grip and fails to meet ever-increasing safety performance requirements.

[0004] To address the shortcomings of the prior art, this invention provides a tread rubber composition with high wet performance. By adding hydrogenated petroleum resin to the tread rubber formulation, and synergistically combining functionalized solution-polymerized styrene-butadiene rubber, reinforcing agents, and silane coupling agents, the invention aims to significantly improve tire grip on wet roads, effectively shorten braking distance, and thus enhance the driving safety of new energy vehicles in rainy and wet conditions. Summary of the Invention

[0005] Therefore, the present invention provides a tread rubber composition with high wet performance to overcome the shortcomings of the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a tread rubber composition with high wet performance is provided, comprising the following raw materials in parts by weight: 100 parts of base rubber; 10-30 parts of hydrogenated petroleum resin; 10 parts of silane coupling agent; 105 parts of reinforcing agent; Anti-aging agent 6 parts; 5 parts surfactant; 0-15 parts of softener; 1 part vulcanizing agent; Accelerator 2.5 parts; Five parts of auxiliary agent.

[0007] Furthermore, the matrix rubber is functionalized solution-polymerized styrene-butadiene rubber.

[0008] Further, the silane coupling agent is selected from at least one of bis-[γ-(triethoxysilyl)propyl]tetrasulfide (e.g., Si69) and bis-[3-(triethoxysilyl)propyl]disulfide (e.g., Si75); the reinforcing agent is selected from at least one of highly dispersed precipitated hydrated silica and carbon black N375; the antioxidant is selected from at least one of physical antioxidants, thermo-oxidative antioxidants, and ozone antioxidants; the activator is selected from at least one of stearic acid and zinc oxide; the softener is an environmentally friendly aromatic oil; and the vulcanizing agent is sulfur (e.g., insoluble sulfur Crystex). TM HS OT 20); the accelerator is selected from at least one of accelerator CZ and accelerator DM; the auxiliary agent is selected from at least one of anti-scorching agent (e.g., anti-scorching agent CTP) and homogenizer (homogenizer H40MSF).

[0009] Further, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide (e.g., Si69); the reinforcing agent is composed of highly dispersed precipitated hydrated silica and carbon black N375; the antioxidant is composed of physical antioxidant, thermo-oxidative antioxidant and ozone antioxidant; the activator is composed of stearic acid (e.g., stearic acid 1801) and zinc oxide; the accelerator is composed of accelerator CZ and accelerator DM; the auxiliary agent is composed of anti-scorching agent (e.g., anti-scorching agent CTP) and homogenizer (homogenizer H40MSF).

[0010] Furthermore, the mass ratio of the highly dispersed precipitated hydrated silica to carbon black N375 is 19:2; the mass ratio of the physical antioxidant, thermo-oxidative antioxidant, and ozone antioxidant is 1:2:3; the mass ratio of the stearic acid to zinc oxide is 2:3; the accelerator is accelerator CZ to accelerator DM with a mass ratio of 2:3; and the mass ratio of the anti-scorching agent (e.g., anti-scorching agent CTP) to the homogenizer (homogenizer H40MSF) is 0.3:4.7.

[0011] Furthermore, the physical antioxidant is selected from at least one of microcrystalline wax (e.g., microcrystalline wax 80#) and rubber protective wax; the thermo-oxidative antioxidant is selected from at least one of antioxidant RD, antioxidant TMQ, antioxidant RD and antioxidant 224; and the ozone antioxidant is selected from at least one of antioxidant 6PPD and antioxidant 4020.

[0012] According to a second aspect of the present invention, a method for preparing a tread rubber composition with high wet performance is provided, comprising the following steps: (1) A stage of mixing Raise the top bolt and add the base rubber at 40-50 r / min, then lower the top bolt and react for 30-40 s; adjust the speed to 35-45 r / min, raise the top bolt, add the reinforcing agent, silane coupling agent, and homogenizer, then lower the top bolt; keep the speed constant and raise the temperature to 90-110℃, raise the top bolt, add carbon black, then lower the top bolt; raise the top bolt, add 30% softener, keep the speed constant and raise the temperature to 100-120℃; raise the top bolt, add the anti-scorching agent, and quickly mix for 20-30 s, then immediately open the discharge gate to discharge the rubber, obtaining a first-stage compound; (2) Two-stage mixing Raise the top bolt, add 70% softener, hydrogenated petroleum resin, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 110-130℃ and adjust the rotation speed to 25-35r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 120-140℃ and adjust the rotation speed to 15-25r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the compound, and obtain the second-stage compound. (3) Final Refinement Raise the top bolt, adjust the rotation speed to 25-35 r / min, add vulcanizing agent and accelerator to the two-stage compound obtained in step (2), lower the top bolt, and react for 30 seconds; adjust the rotation speed to 20-30 r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 100-110℃, open the discharge door to discharge the rubber, and obtain the final compound; (4) Refining The final rubber obtained in step (3) is subjected to open milling at 95-105℃, and the thickness of the rubber sheet is set to 2-3mm. The rubber sheet is then passed through a mill and formed into a triangular shape. This process is repeated 8-12 times. Finally, the sheet is extruded to obtain the tread rubber composition.

[0013] The method of using the tread rubber composition is as follows: The obtained tread rubber composition was vulcanized at 155-165°C and 95-105 PSI for 12-18 minutes.

[0014] According to a third aspect of the invention, the application of the tread rubber composition prepared by the method described above is provided in tire production.

[0015] Compared with the prior art, the present invention has the following advantages: (1) The hydrogenated petroleum resin used in this invention (especially C9 hydrogenated petroleum resin and C5 / C9 copolymer hydrogenated resin) contains rigid groups such as styrene, methylstyrene, indene, and methylindene, and has a high glass transition temperature (Tg) (20-60℃). After blending with the rubber matrix, the overall Tg of the rubber compound can be increased through the physical entanglement of molecular chains, so that the rubber compound is in the viscoelastic state near 0℃. At this temperature, the material exhibits excellent energy dissipation ability, which is closely related to the wet grip performance of the tire. Under dynamic strain, the speed of movement adjustment of rubber molecular chain segments cannot keep up with the strain frequency, thereby increasing the hysteresis loss and significantly increasing the loss factor (tanδ@0℃) in the 0℃ range. The dynamic mechanical property test results show that the tanδ@0℃ of the groups in Examples 1-3 is increased by 31.3%, 15.9% and 7.9% respectively compared with the comparative group (0.466), and the wet grip index (based on the comparative group as 100%) is increased to 131%, 116% and 108% respectively.

[0016] (2) Based on the improvement of tanδ@0℃, the energy dissipation capacity and adhesion of the tire on wet and slippery roads are enhanced, and the wet braking distance of the actual vehicle is significantly shortened. The application performance test results show that the wet braking distance of the groups in Examples 1-3 is shortened by 6.4%, 2.9% and 1.3% respectively compared with the comparative group (45.2m).

[0017] (3) The improvement of the dynamic mechanical properties of the rubber compound by hydrogenated petroleum resin is also reflected in dry braking. The application performance test results show that the dry braking distance of the groups in Examples 1-3 was shortened by 2.6%, 1.6% and 0.8% respectively compared with the comparative group (37.8m), and the dry braking performance (based on the comparative group as 100%) was improved to 103%, 102% and 101% respectively.

[0018] (4) Hydrogenated petroleum resin has good compatibility with commonly used rubbers such as styrene-butadiene rubber (SBR). Its molecular chain contains a small number of polar groups, which can form hydrogen bonds with the silanol groups on the surface of silica (such as highly dispersed precipitated hydrated silica), and at the same time, it can be mutually dissolved and entangled with the rubber molecular chain, playing an interfacial bridging role, promoting the uniform dispersion of silica in the rubber matrix, and reducing filler agglomeration. The uniformly dispersed filler network can improve the cohesive strength of the rubber compound, so that the tread maintains a stable contact shape when under pressure on wet and slippery road surfaces, further optimizing wet grip performance.

[0019] (5) By adjusting the replacement ratio of hydrogenated petroleum resin and environmentally friendly aromatic oil, the processing performance, vulcanization characteristics, mechanical properties, and dynamic viscoelasticity of the rubber compound can be controlled within a certain range to meet different performance requirements. Specifically, the hydrogenated petroleum resin substitution scheme can increase Mooney viscosity, MH, and T50 with the increase of hydrogenated petroleum resin content, and the overall fluctuation of the 300% constant elongation stress is relatively small (100-102 kgf / cm). 2The Shore hardness remained unchanged (69A). This indicates that high addition levels (10-30 parts) of hydrogenated petroleum resin did not lead to excessive softening of the compound due to the increased substitution amount. This is attributed to the rigid skeletal structure and high glass transition temperature of the hydrogenated petroleum resin itself, which allows it to maintain or even enhance the cohesive strength and dimensional stability of the compound while performing plasticizing / compensating functions. This alternative can effectively improve the strength and toughness of the compound without sacrificing material rigidity.

[0020] (6) DMA analysis showed that tanδ@60℃ (characterizing rolling resistance) increased with the increase of hydrogenated petroleum resin content. However, compared with the comparative group (0.466), the increase of tanδ@0℃ (7.9%-31.3%) was significantly greater than that of tanδ@60℃ (4.2%-11.1%). This indicates that while improving wet braking performance, the increase of rolling resistance is relatively limited, and the wet braking performance and rolling resistance can be controlled and adjusted. Detailed Implementation

[0021] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] According to a first aspect of the present invention, a tread rubber composition with high wet performance is provided, comprising the following raw materials in parts by weight: 100 parts of base rubber; 10-30 parts of hydrogenated petroleum resin; 10 parts of silane coupling agent; 105 parts of reinforcing agent; Anti-aging agent 6 parts; 5 parts surfactant; 0-15 parts of softener; 1 part vulcanizing agent; Accelerator 2.5 parts; Five parts of auxiliary agent.

[0023] Furthermore, the base rubber is functionalized solution-polymerized styrene-butadiene rubber.

[0024] Furthermore, the silane coupling agent is selected from at least one of bis-[γ-(triethoxysilyl)propyl]tetrasulfide (e.g., Si69) and bis-[3-(triethoxysilyl)propyl]disulfide (e.g., Si75); the reinforcing agent is selected from at least one of highly dispersed precipitated hydrated silica and carbon black N375; the antioxidant is selected from at least one of physical antioxidants, thermo-oxidative antioxidants, and ozone antioxidants; the activator is selected from at least one of stearic acid and zinc oxide; the softener is an environmentally friendly aromatic oil; and the vulcanizing agent is sulfur (e.g., insoluble sulfur Crystex). TM HS OT 20); the accelerator is selected from at least one of accelerator CZ and accelerator DM; the auxiliary agent is selected from at least one of anti-scorching agent (e.g., anti-scorching agent CTP) and homogenizer (homogenizer H40MSF).

[0025] Furthermore, the silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide (e.g., Si69); the reinforcing agent is composed of highly dispersed precipitated hydrated silica and carbon black N375; the antioxidant is composed of physical antioxidant, thermo-oxidative antioxidant and ozone antioxidant; the activator is composed of stearic acid (e.g., stearic acid 1801) and zinc oxide; the accelerator is composed of accelerator CZ and accelerator DM; the auxiliary agent is composed of anti-scorching agent (e.g., anti-scorching agent CTP) and homogenizer (homogenizer H40MSF).

[0026] Furthermore, the mass ratio of highly dispersed hydrated silica to carbon black N375 is 19:2; the mass ratio of physical antioxidant, thermo-oxidative antioxidant, and ozone antioxidant is 1:2:3; the mass ratio of stearic acid to zinc oxide is 2:3; the mass ratio of accelerator CZ to accelerator DM is 2:3; and the mass ratio of scorch inhibitor (e.g., scorch inhibitor CTP) to homogenizer (homogenizer H40MSF) is 0.3:4.7.

[0027] Furthermore, the physical antioxidant is selected from at least one of microcrystalline wax (e.g., microcrystalline wax 80#) and rubber protective wax; the thermo-oxidative antioxidant is selected from at least one of antioxidant RD, antioxidant TMQ, antioxidant RD and antioxidant 224; and the ozone antioxidant is selected from at least one of antioxidant 6PPD and antioxidant 4020.

[0028] According to a second aspect of the present invention, a method for preparing a tread rubber composition with high wet performance is provided, comprising the following steps: (1) A stage of mixing Raise the top bolt and add the base rubber at 40-50 r / min. Lower the top bolt and react for 30-40 s. Adjust the speed to 35-45 r / min, raise the top bolt, add the reinforcing agent, silane coupling agent, and homogenizer, and lower the top bolt. Raise the top bolt, add 30% softener, keep the speed constant, and heat to 90-110℃. Raise the top bolt, add carbon black, and lower the top bolt. Keep the speed constant and heat to 100-120℃. Raise the top bolt, add the anti-scorching agent, and quickly mix for 20-30 s. Immediately open the discharge gate to discharge the rubber, obtaining a first-stage compound. (2) Two-stage mixing Raise the top bolt, add 70% softener, hydrogenated petroleum resin, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 110-130℃ and adjust the rotation speed to 25-35r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 120-140℃ and adjust the rotation speed to 15-25r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the compound, and obtain the second-stage compound. (3) Final Refinement Raise the top bolt, adjust the rotation speed to 25-35 r / min, add vulcanizing agent and accelerator to the two-stage compound obtained in step (2), lower the top bolt, and react for 30 seconds; adjust the rotation speed to 20-30 r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 100-110℃, open the discharge door to discharge the rubber, and obtain the final compound; (4) Refining The final rubber obtained in step (3) is subjected to open milling at 95-105℃, and the thickness of the rubber sheet is set to 2-3mm. The rubber sheet is then passed through a mill and formed into a triangular shape. This process is repeated 8-12 times. Finally, the sheet is extruded to obtain the tread rubber composition.

[0029] The method of using the tread rubber composition is as follows: The obtained tread rubber composition was vulcanized at 155-165°C and 95-105 PSI for 12-18 minutes.

[0030] According to a third aspect of the invention, the application of the tread rubber composition prepared by the method is provided in tire production.

[0031] The reagents used in this invention are as follows: Functionalized solution-polymerized styrene-butadiene rubber (styrene content >25%, vinyl content >60%, Mooney viscosity ML(1+4) 100℃ is 60, oil content in styrene-butadiene rubber is 27%) was prepared in our laboratory. Hydrogenated petroleum resin (pale yellow granules, softening point 120℃) was purchased from Tianjin Zhongke New Materials Co., Ltd. The silane coupling agent Si69, the anti-scorching agent CTP, and the homogenizer H40MSF were all purchased from Shandong Yanggu Huatai Chemical Co., Ltd. Insoluble sulfur Crystex TM HS OT 20 (20% oil-extended, 80% sulfur content, high-temperature sulfur content ≥65%), highly dispersed precipitated hydrated silica ULTRASIL @ 9100 (BET specific surface area ≥ 200m²) 2 / g, CTAB compressible surface area ≥180m² 2 / g, pH value 6.0-7.0), all purchased from Shanghai Kaiyin Chemical Co., Ltd.; Environmentally friendly aromatic oil, purchased from Shandong Taichang Petrochemical Technology Co., Ltd. Carbon black N375 (DBP oil absorption value ≥110mL / 100g, iodine absorption value ≥90mg / g) was purchased from Guangzhou Jingyi New Materials Co., Ltd. Microcrystalline wax 80#, antioxidant RD, antioxidant 6PPD, stearic acid 1801, zinc oxide, accelerator CZ, and accelerator DM were all purchased from Jining Tangyi Chemical Co., Ltd.

[0032] To better illustrate the technical effects of this invention, the following embodiments are provided.

[0033] Preparation Example 1 Preparation of functionalized solution-polymerized styrene-butadiene rubber Under a nitrogen atmosphere, 150 kg of cyclohexane solvent (solid content controlled at 16%) was added to a dry polymerization reactor, and the system temperature was controlled at (30±2) °C. 8.8 kg of styrene and 21.4 kg of butadiene monomer were added sequentially, and after thorough stirring, 150 mL of 1.6 M n-butyllithium (initiator) was added to initiate polymerization. 0.52 kg of tetrahydrofuran (THF) was added as a structure modifier, and the THF / Li molar ratio was controlled to ensure that the vinyl content in the copolymer was greater than 60%. The polymerization reaction was exothermic, with the maximum reaction temperature controlled at (75±2) °C, and the reaction time was 1.5 h. 15.6 g of tin tetrachloride (SnCl4, purity ≥99%) was added to the active polymer solution for a coupling reaction, with the Sn / Li molar ratio controlled at 0.25∶1, and the reaction time was 30 min. The reaction was terminated by adding 80 mL of ethanol (terminant), and then 8.6 kg of environmentally friendly aromatic oil was added for oil filling treatment. The solvent was removed by steam condensation and the product was extruded and dried to obtain functionalized solution-polymerized styrene-butadiene rubber, approximately 40.6 kg.

[0034] Note: All the above reagents have undergone strict dehydration and deoxygenation treatment.

[0035] Example 1 The tread rubber composition in this embodiment includes the following components: 10 kg of functionalized solution-polymerized styrene-butadiene rubber; 3 kg of hydrogenated petroleum resin; Silane coupling agent Si69 1kg; 10.5 kg of reinforcing agent; Anti-aging agent 0.6kg; Surfactant 0.5kg; Insoluble sulfur Crystex TM HS OT 20 0.1kg; Accelerator 0.25kg; CTP anti-scorching agent 0.03kg; Homogenizer H40MSF 0.47kg.

[0036] The reinforcing agent consists of 9.5 kg of highly dispersed precipitated hydrated silica and 1 kg of carbon black N375; the antioxidant consists of 0.1 kg of microcrystalline wax 80#, 0.2 kg of antioxidant RD and 0.3 kg of antioxidant 6PPD; the activator consists of 0.2 kg of stearic acid 1801 and 0.3 kg of zinc oxide; and the accelerator consists of 0.1 kg of accelerator CZ and 0.15 kg of accelerator DM.

[0037] Its preparation method is as follows: (1) Raise the top plug and add the functionalized solution polystyrene-butadiene rubber obtained in Preparation Example 1 at 45 r / min. Lower the top plug and mix for 35 s. Adjust the speed to 40 r / min, raise the top plug, add highly dispersed precipitated hydrated silica, silane coupling agent Si69 and homogenizer H40MSF, and lower the top plug. Keep the speed constant and raise the temperature to 100 ℃. Raise the top plug and add carbon black N375, and lower the top plug. Keep the speed constant and raise the temperature to 110 ℃. Raise the top plug and add anti-scorching agent CTP. Mix quickly for 25 s. Immediately open the discharge door to discharge the rubber and obtain a section of mixed rubber. (2) Raise the top bolt, add hydrogenated petroleum resin, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 120℃ and adjust the speed to 30r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 130℃ and adjust the speed to 20r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the rubber, and obtain the second-stage compound. (3) Raise the top bolt, adjust the rotation speed to 30 r / min, and add insoluble sulfur Crystex to the two-stage compound obtained in step (2). TM Add HS OT 20 and accelerator, lower the top plug, and react for 30 seconds; adjust the rotation speed to 25 r / min, raise the top plug, clean, and lower the top plug; raise the temperature to 105℃, open the discharge door to discharge the rubber, and obtain the final compound. (4) The final rubber obtained in step (3) is processed at 100°C and the thickness of the rubber sheet is set to 2 mm. The rubber sheet is thinned and rolled into a triangular shape on the open mill. The operation is repeated 10 times. The last sheet is produced to obtain the tread rubber composition.

[0038] Its usage method is as follows: The tread rubber composition obtained above was vulcanized at 160°C and 100 PSI for 15 min.

[0039] Example 2 The tread rubber composition in this embodiment includes the following components: 10 kg of functionalized solution-polymerized styrene-butadiene rubber; 2 kg of hydrogenated petroleum resin; Silane coupling agent Si69 1kg; 10.5 kg of reinforcing agent; Anti-aging agent 0.6kg; Surfactant 0.5kg; 0.5 kg of environmentally friendly aromatic oil; Insoluble sulfur Crystex TM HS OT 20 0.1kg; Accelerator 0.25kg; CTP anti-scorching agent 0.03kg; Homogenizer H40MSF 0.47kg.

[0040] The reinforcing agent consists of 9.5 kg of highly dispersed precipitated hydrated silica and 1 kg of carbon black N375; the antioxidant consists of 0.1 kg of microcrystalline wax 80#, 0.2 kg of antioxidant RD and 0.3 kg of antioxidant 6PPD; the activator consists of 0.2 kg of stearic acid 1801 and 0.3 kg of zinc oxide; and the accelerator consists of 0.1 kg of accelerator CZ and 0.15 kg of accelerator DM.

[0041] Its preparation method is as follows: (1) Raise the top plug and add the functionalized solution polystyrene-butadiene rubber obtained in Preparation Example 1 at 45 r / min. Lower the top plug and mix for 35 s. Adjust the speed to 40 r / min, raise the top plug, add highly dispersed precipitated hydrated silica, silane coupling agent Si69 and homogenizer H40MSF, and lower the top plug. Raise the top plug, add 30% environmentally friendly aromatic oil, keep the speed constant, raise the temperature to 100°C, raise the top plug, add carbon black N375, and lower the top plug. Keep the speed constant, raise the temperature to 110°C. Raise the top plug, add anti-scorching agent CTP, mix quickly for 25 s, and immediately open the discharge door to discharge the rubber to obtain a section of mixed rubber. (2) Raise the top bolt, add 70% environmentally friendly aromatic oil, hydrogenated petroleum resin, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 120℃ and adjust the speed to 30r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 130℃ and adjust the speed to 20r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the rubber, and obtain the second-stage compound; (3) Raise the top bolt, adjust the rotation speed to 30 r / min, and add insoluble sulfur Crystex to the two-stage compound obtained in step (2). TM Add HS OT 20 and accelerator, lower the top plug, and react for 30 seconds; adjust the rotation speed to 25 r / min, raise the top plug, clean, and lower the top plug; raise the temperature to 105℃, open the discharge door to discharge the rubber, and obtain the final compound. (4) The final rubber obtained in step (3) is processed at 100°C and the thickness of the rubber sheet is set to 2 mm. The rubber sheet is thinned and rolled into a triangular shape on the open mill. The operation is repeated 10 times. The last sheet is produced to obtain the tread rubber composition.

[0042] Its usage method is as follows: The tread rubber composition obtained above was vulcanized at 160°C and 100 PSI for 15 min.

[0043] Example 3 The tread rubber composition in this embodiment includes the following components: 10 kg of functionalized solution-polymerized styrene-butadiene rubber; 1 kg of hydrogenated petroleum resin; Silane coupling agent Si69 1kg; 10.5 kg of reinforcing agent; Anti-aging agent 0.6kg; Surfactant 0.5kg; 1 kg of environmentally friendly aromatic oil; Insoluble sulfur Crystex TM HS OT 20 0.1kg; Accelerator 0.25kg; CTP anti-scorching agent 0.03kg; Homogenizer H40MSF 0.47kg.

[0044] The reinforcing agent consists of 9.5 kg of highly dispersed precipitated hydrated silica and 1 kg of carbon black N375; the antioxidant consists of 0.1 kg of microcrystalline wax 80#, 0.2 kg of antioxidant RD and 0.3 kg of antioxidant 6PPD; the activator consists of 0.2 kg of stearic acid 1801 and 0.3 kg of zinc oxide; and the accelerator consists of 0.1 kg of accelerator CZ and 0.15 kg of accelerator DM.

[0045] Its preparation method is as follows: (1) Raise the top plug and add the functionalized solution polystyrene-butadiene rubber obtained in Preparation Example 1 at 45 r / min. Lower the top plug and mix for 35 s. Adjust the speed to 40 r / min, raise the top plug, add highly dispersed precipitated hydrated silica, silane coupling agent Si69 and homogenizer H40MSF, and lower the top plug. Raise the top plug, add 30% environmentally friendly aromatic oil, keep the speed constant, raise the temperature to 100°C, raise the top plug, add carbon black N375, and lower the top plug. Keep the speed constant, raise the temperature to 110°C. Raise the top plug, add anti-scorching agent CTP, mix quickly for 25 s, and immediately open the discharge door to discharge the rubber to obtain a section of mixed rubber. (2) Raise the top bolt, add 70% environmentally friendly aromatic oil, hydrogenated petroleum resin, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 120℃ and adjust the speed to 30r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 130℃ and adjust the speed to 20r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the rubber, and obtain the second-stage compound; (3) Raise the top bolt, adjust the rotation speed to 30 r / min, and add insoluble sulfur Crystex to the two-stage compound obtained in step (2). TM Add HS OT 20 and accelerator, lower the top plug, and react for 30 seconds; adjust the rotation speed to 25 r / min, raise the top plug, clean, and lower the top plug; raise the temperature to 105℃, open the discharge door to discharge the rubber, and obtain the final compound. (4) The final rubber obtained in step (3) is processed at 100°C and the thickness of the rubber sheet is set to 2 mm. The rubber sheet is thinned and rolled into a triangular shape on the open mill. The operation is repeated 10 times. The last sheet is produced to obtain the tread rubber composition.

[0046] Its usage method is as follows: The tread rubber composition obtained above was vulcanized at 160°C and 100 PSI for 15 min.

[0047] Comparative Example The tread rubber composition in this embodiment includes the following components: 10 kg of functionalized solution-polymerized styrene-butadiene rubber; Silane coupling agent Si69 1kg; 10.5 kg of reinforcing agent; Anti-aging agent 0.6kg; Surfactant 0.5kg; 1.5 kg of environmentally friendly aromatic oil; Insoluble sulfur Crystex TM HS OT 20 0.1kg; Accelerator 0.25kg; CTP anti-scorching agent 0.03kg; Homogenizer H40MSF 0.47kg.

[0048] The reinforcing agent consists of 9.5 kg of highly dispersed precipitated hydrated silica and 1 kg of carbon black N375; the antioxidant consists of 0.1 kg of microcrystalline wax 80#, 0.2 kg of antioxidant RD and 0.3 kg of antioxidant 6PPD; the activator consists of 0.2 kg of stearic acid 1801 and 0.3 kg of zinc oxide; and the accelerator consists of 0.1 kg of accelerator CZ and 0.15 kg of accelerator DM.

[0049] Its preparation method is as follows: (1) Raise the top plug and add the functionalized solution polystyrene-butadiene rubber obtained in Preparation Example 1 at 45 r / min. Lower the top plug and mix for 35 s. Adjust the speed to 40 r / min, raise the top plug, add highly dispersed precipitated hydrated silica, silane coupling agent Si69 and homogenizer H40MSF, and lower the top plug. Raise the top plug, add 30% environmentally friendly aromatic oil, keep the speed constant, raise the temperature to 100°C, raise the top plug, add carbon black N375, and lower the top plug. Keep the speed constant, raise the temperature to 110°C. Raise the top plug, add anti-scorching agent CTP, mix quickly for 25 s, and immediately open the discharge door to discharge the rubber to obtain a section of mixed rubber. (2) Raise the top bolt, add 70% environmentally friendly aromatic oil, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 120℃ and adjust the speed to 30r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 130℃ and adjust the speed to 20r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the rubber, and obtain the second-stage compound; (3) Raise the top bolt, adjust the rotation speed to 30 r / min, and add insoluble sulfur Crystex to the two-stage compound obtained in step (2). TM Add HS OT 20 and accelerator, lower the top plug, and react for 30 seconds; adjust the rotation speed to 25 r / min, raise the top plug, clean, and lower the top plug; raise the temperature to 105℃, open the discharge door to discharge the rubber, and obtain the final compound. (4) The final rubber obtained in step (3) is processed at 100°C and the thickness of the rubber sheet is set to 2 mm. The rubber sheet is thinned and rolled into a triangular shape on the open mill. The operation is repeated 10 times. The last sheet is produced to obtain the tread rubber composition.

[0050] Its usage method is as follows: The tread rubber composition obtained above was vulcanized at 160°C and 100 PSI for 15 min.

[0051] Test Example 1 Processing performance To evaluate the processing performance of the tread rubber composition of the present invention, the Mooney viscosity and vulcanization properties of the tread rubber compositions in Examples 1-3 and the comparative example group were tested. The specific test methods are as follows: (1) Mooney viscosity test To characterize the viscosity and processing ease of rubber, referring to GB / T 1232.1-2016 "Determination of Uncured Rubber Using a Disk Shear Viscometer - Part 1: Determination of Mooney Viscosity", the tread rubber composition from each experimental group was preheated in a mold cavity at 100℃ for 1 min, and then the rotor was started to rotate (2 r / min) for 4 min. The torque value of the tread rubber composition was measured and recorded using a Mooney viscometer and denoted as Mooney viscosity ML(1+4)100℃. Three parallel samples were set up for each group, and the results are expressed as mean ± standard deviation.

[0052] (2) Vulcanization performance test To characterize the vulcanization properties (vulcanization rate and degree of crosslinking) of rubber, referring to GB / T 9869.3-2025 "Determination of vulcanization properties of rubber using a vulcanizing apparatus - Part 3: Rotorless vulcanizing apparatus", the tread rubber compositions from each experimental group were tested using a rotorless rheometer (model: MDR2000) at a temperature of 160℃, an oscillation frequency of 1.67Hz, and an oscillation angle of ±0.5°. The following parameters were recorded: Minimum torque (ML, dN·m): reflects the viscosity of the tread rubber composition at the start of vulcanization; Maximum torque (MH, dN·m): reflects the hardness and degree of cross-linking of the tread rubber composition after vulcanization; T50 (min): Torque rises from ML to The time required to complete the process characterizes the intermediate rate of the sulfidation reaction.

[0053] Each group has 3 parallel samples, expressed as mean ± standard deviation.

[0054] The test results are shown in Table 1 below: Table 1. Results of processing performance tests of tread rubber compositions in each experimental group.

[0055] It can be seen from Table 1 above: Compared to the comparative group (82±0.3), the Mooney viscosity of the tread rubber compositions in Examples 1-3 was in the range of 81-84 mL (1+4) at 100°C. Specifically, the Mooney viscosity increased by 2.4% and 1.2% in Examples 1 and 2, respectively, while it decreased by 1.2% in Example 3. Compared to the comparative group (21.5±0.09), the Mooney viscosity (MH) of the tread rubber compositions in Examples 1-3 was in the range of 21.2-22.2 dN·m. Specifically, the MH increased by 3.3% and 2.3% in Examples 1 and 2, respectively, while it decreased by 1.4% in Example 3. Compared to the comparative group (1.47±0.04), the T50 of the tread rubber compositions in Examples 1-3 was in the range of 1.48-1.52 min, representing increases of 3.4%, 2%, and 0.7%, respectively.

[0056] The above results indicate that the Mooney viscosity, MH, and T50 of the tread rubber composition of the present invention increase with the increase of the amount of hydrogenated petroleum resin. The hydrogenated petroleum resin substitution scheme can appropriately increase the processing viscosity, crosslinking density, and vulcanization rate of the tread rubber composition, and the processing performance and vulcanization characteristics can be controlled by adjusting the amount of hydrogenated petroleum resin.

[0057] Test Example 2 Material properties To evaluate the material properties of the tread rubber composition of the present invention, the hardness and tensile properties of the tread rubber compositions in Examples 1-3 and the comparative example group were tested. The specific test methods are as follows: (1) Hardness test To characterize the hardness properties of rubber, referring to GB / T 39693.4-2025 "Determination of Hardness of Vulcanized Rubber or Thermoplastic Rubber - Part 4: Determination of Indentation Hardness by Shore Hardness Tester (Shore Hardness)," the tread rubber composition from each experimental group was vulcanized at 160℃ and 100 PSI for 15 min to obtain vulcanized samples. Samples with dimensions of 150mm × 150mm × 2mm (length × width × thickness) were cut from these vulcanized samples and tested using a Shore A hardness tester. The Shore hardness (A) was recorded. Three parallel samples were set up for each group, and the results are expressed as mean ± standard deviation.

[0058] (2) Tensile property test To characterize the strength, tensile strength, and other mechanical properties of rubber, referring to GB / T 528-2009 "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber", the tread rubber composition from each experimental group was vulcanized at 160℃ and 100 PSI for 15 min to obtain vulcanized samples. These vulcanized samples were then cut into type 1A dumbbell-shaped specimens. Testing was performed using an electronic universal tensile testing machine, and the stress at 300% elongation (kgf / cm²) was recorded. 2 Parameters such as tensile strength (kgf) and elongation at break (%) were used. Three parallel samples were set up for each group, and the results are expressed as mean ± standard deviation.

[0059] The test results are shown in Table 2 below: Table 2. Material property test results of samples in each experimental group (n=3)

[0060] It can be seen from Table 2 above: Compared to the comparative example group (69±0.7), the Shore hardness of the samples in Examples 1-3 was 69A. Compared to the comparative example group (102±3), the 300% tensile stress of the samples in Examples 1-3 was between 100-102 kgf / cm². 2 Within the specified range. Among them, Example 2 group was comparable to the comparative example, while Example 1 and Example 3 groups showed decreases of 2% and 1% respectively, with relatively small overall fluctuations. Compared to the comparative example group (205±9), the tensile strength of the samples in Example 1-3 groups was within the range of 210-214 kgf, representing increases of 4.4%, 2.4%, and 2.9% respectively. Compared to the comparative example group (518±26), the elongation at break of the samples in Example 1-3 groups was within the range of 523%-527%, representing increases of 1.7%, 1.0%, and 1.2% respectively.

[0061] The above results indicate that the tread rubber composition of the present invention is essentially equivalent to the comparative group in terms of Shore hardness, but superior to the comparative group in terms of 300% tensile stress, tensile strength, and elongation at break. Furthermore, the tensile strength and elongation at break increase with increasing hydrogenated petroleum resin content. This confirms that the present invention, by replacing environmentally friendly aromatic oils with hydrogenated petroleum resin, can effectively improve the strength and toughness of the rubber compound without sacrificing material rigidity, and that the material properties can be controllably adjusted by regulating the amount of hydrogenated petroleum resin.

[0062] Test Example 3 Dynamic mechanical performance testing To evaluate the dynamic mechanical properties of the tread rubber composition of the present invention, the braking performance and rolling resistance of the tread rubber compositions in Examples 1-3 and the comparative example group were tested. The specific test methods are as follows: To characterize the dynamic mechanical properties of rubber, referring to GB / T 9870.1-2006 "Determination of Dynamic Properties of Vulcanized Rubber or Thermoplastic Rubber Part 1: General Rules", the tread rubber composition from each experimental group was vulcanized at 160℃ and 100 PSI for 15 min to obtain vulcanized samples. These vulcanized samples were cut into rectangular specimens of 10mm × 2mm × 2mm (length × width × thickness). A DMA tester was used in tensile mode at a temperature range of -80℃ to 80℃, a heating rate of 2℃ / min, and a frequency of 11Hz. The loss factor (tanδ) at 0℃ and 60℃ was recorded. The wet grip index (%) was calculated using the following formula: ; Each group has 3 parallel samples, expressed as mean ± standard deviation.

[0063] The test results are shown in Table 3 below: Table 3. Dynamic mechanical property test results of rectangular specimens in each experimental group (n=3)

[0064] It can be seen from Table 3 above: Compared with the comparative example group (0.466±0.012), the tanδ@0℃ of the rectangular samples in Examples 1-3 were in the range of 0.503-0.612, representing increases of 31.3%, 15.9%, and 7.9%, respectively. Compared with the comparative example group (0.144±0.013), the tanδ@60℃ of the rectangular samples in Examples 1-3 were in the range of 0.150-0.160, representing increases of 11.1%, 7.6%, and 4.2%, respectively. Compared with the comparative example group (100±4), the wetland grip index of the rectangular samples in Examples 1-3 were in the range of 108%-131%, representing increases of 31%, 16%, and 8%, respectively.

[0065] The above results indicate that the tread rubber composition of the present invention is superior to the comparative group in terms of tanδ@0℃ and wet grip index. Both tanδ@0℃ and wet grip index increase with increasing hydrogenated petroleum resin content. Further analysis of the tanδ@60℃ trend shows an overall upward trend, but the increase is less than that of tanδ@0℃, indicating that the present invention improves wet braking performance while having a relatively limited increase in rolling resistance. This confirms that the present invention, by replacing environmentally friendly aromatic oil with hydrogenated petroleum resin, can achieve controllable adjustment of wet braking performance and rolling resistance while significantly improving wet braking performance.

[0066] Test Example 4 Application performance To evaluate the application performance of the tread rubber composition of the present invention, the wet braking distance, wet braking performance, dry braking distance, and dry braking performance of the tread rubber compositions in Examples 1-3 and the comparative example group were tested. The tread rubber compositions from Examples 1-3 and the comparative example group were vulcanized at 160°C and 100 PSI for 15 minutes to prepare finished tires (tire specification: 205 / 55 R16), which were then mounted on the same test vehicle for real-vehicle road testing. Each group underwent the same mileage break-in period before testing, and each group underwent three effective braking tests. Results are expressed as mean ± standard deviation. The specific testing methods are as follows: (1) Wet braking test To characterize the longitudinal grip and linear drainage performance of tires on wet roads, tests were conducted in accordance with GB 21670-2025 "Technical Requirements and Test Methods for Braking Systems of Passenger Cars" and GB / T 21910-2017 "Test Method for Relative Grip Performance of Passenger Car Tires on Wet Roads". The test vehicle underwent emergency braking at an initial speed of 100 km / h on a wet asphalt road surface with a water film thickness of 1 mm. The braking distance (m) from brake pedal activation to complete vehicle stop was recorded, along with the fully applied average deceleration (MFDD). Wet braking performance (%) was calculated using the following formula: ; (2) Dry braking test To characterize the longitudinal grip of tires on dry roads, tests were conducted in accordance with GB 21670-2025 "Technical Requirements and Test Methods for Braking Systems of Passenger Cars" and T / CRIA 29017-2025 "Test Method for Braking Distance of Automobile Tires on Dry Roads". The test vehicle was subjected to emergency braking at an initial speed of 100 km / h on a dry, clean asphalt road surface (coefficient of adhesion ≥ 0.7, road slope ≤ 1%). The braking distance (m) from the moment the brake pedal was pressed to the moment the vehicle came to a complete stop was recorded, along with the fully exerted average deceleration (MFDD). The dry braking performance (%) was calculated using the following formula: ; The test results are shown in Table 4 below: Table 4. Test results of the application performance of finished tires in each experimental group (n=3)

[0067] Note: In the actual testing process, the MFDD test values ​​of each group all met the requirements of GB 21670-2025 standard.

[0068] It can be seen from Table 4 above: Compared to the comparative group (45.2±0.4), the wet braking distances of the finished tires in Examples 1-3 were in the range of 42.3-44.6m, representing reductions of 6.4%, 2.9%, and 1.3%, respectively. Compared to the comparative group (100±3), the wet braking performance of the finished tires in Examples 1-3 was in the range of 101%-107%, representing improvements of 7%, 3%, and 1%, respectively. Compared to the comparative group (37.8±0.2), the dry braking distances of the finished tires in Examples 1-3 were in the range of 36.8-37.5m, representing reductions of 2.6%, 1.6%, and 0.8%, respectively. Compared to the comparative group (100±2), the dry braking performance of the finished tires in Examples 1-3 was in the range of 101%-103%, representing improvements of 3%, 2%, and 1%, respectively.

[0069] The above results show that the tread rubber composition of the present invention is superior to the comparative group in both wet and dry braking distances, and also superior in both wet and dry braking performance. Furthermore, both wet and dry braking distances decrease with increasing amounts of hydrogenated petroleum resin, while both wet and dry braking performance improve with increasing amounts of hydrogenated petroleum resin. This confirms that the present invention, by replacing environmentally friendly aromatic oils with hydrogenated petroleum resin, can effectively shorten both wet and dry braking distances and improve braking performance, and that the braking performance can be controllably adjusted by regulating the amount of hydrogenated petroleum resin.

[0070] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.

Claims

1. A tread rubber composition with high wet performance, characterized in that, Including the following parts by weight of raw materials: 100 parts of base rubber; 10-30 parts of hydrogenated petroleum resin; 10 parts of silane coupling agent; 105 parts of reinforcing agent; Anti-aging agent 6 parts; 5 parts surfactant; 0-15 parts of softener; 1 part vulcanizing agent; Accelerator 2.5 parts; Five parts of auxiliary agent.

2. The tread rubber composition according to claim 1, characterized in that, The matrix rubber is functionalized solution-polymerized styrene-butadiene rubber.

3. The tread rubber composition according to claim 1, characterized in that, The silane coupling agent is selected from at least one of bis-[γ-(triethoxysilyl)propyl]tetrasulfide and bis-[3-(triethoxysilyl)propyl]disulfide; the reinforcing agent is selected from at least one of highly dispersed precipitated hydrated silica and carbon black N375; the antioxidant is selected from at least one of physical antioxidants, thermo-oxidative antioxidants, and ozone antioxidants; the activator is selected from at least one of stearic acid and zinc oxide; the softener is environmentally friendly aromatic oil; the vulcanizing agent is sulfur; the accelerator is selected from at least one of accelerator CZ and accelerator DM; and the auxiliary agent is selected from at least one of anti-scorching agent and homogenizing agent.

4. The tread rubber composition according to claim 3, characterized in that, The silane coupling agent is bis-[γ-(triethoxysilyl)propyl]tetrasulfide; the reinforcing agent is composed of highly dispersed precipitated hydrated silica and carbon black N375; the antioxidant is composed of physical antioxidant, thermo-oxidative antioxidant and ozone antioxidant; the activator is composed of stearic acid and zinc oxide; the accelerator is composed of accelerator CZ and accelerator DM; the auxiliary agent is composed of anti-scorching agent and homogenizer.

5. The tread rubber composition according to claim 4, characterized in that, The mass ratio of the highly dispersed precipitated hydrated silica to carbon black N375 is 19:2; the mass ratio of the physical antioxidant, thermo-oxidative antioxidant, and ozone antioxidant is 1:2:3; the mass ratio of the stearic acid to zinc oxide is 2:3; the mass ratio of the accelerator CZ to the accelerator DM is 2:3; and the mass ratio of the anti-scorching agent to the homogenizer is 0.3:4.

7.

6. The tread rubber composition as described in claim 5, characterized in that, The physical antioxidant is selected from at least one of microcrystalline wax and rubber protective wax; the thermo-oxidative antioxidant is selected from at least one of antioxidant RD, antioxidant TMQ, antioxidant RD and antioxidant 224; the ozone antioxidant is selected from at least one of antioxidant 6PPD and antioxidant 4020.

7. A method for preparing a tread rubber composition with high wet performance, suitable for preparing the tread rubber composition as described in claims 1-6, characterized in that, Includes the following steps: (1) A stage of mixing Raise the top bolt and add the base rubber at 40-50 r / min, then lower the top bolt and react for 30-40 s; adjust the speed to 35-45 r / min, raise the top bolt, add the reinforcing agent, silane coupling agent, and homogenizer, then lower the top bolt; keep the speed constant and raise the temperature to 90-110℃, raise the top bolt, add carbon black, then lower the top bolt; raise the top bolt, add 30% softener, keep the speed constant and raise the temperature to 100-120℃; raise the top bolt, add the anti-scorching agent, and quickly mix for 20-30 s, then immediately open the discharge gate to discharge the rubber, obtaining a first-stage compound; (2) Two-stage mixing Raise the top bolt, add 70% softener, hydrogenated petroleum resin, antioxidant and activator to the first-stage compound obtained in step (1), and lower the top bolt; raise the temperature to 110-130℃ and adjust the rotation speed to 25-35r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 120-140℃ and adjust the rotation speed to 15-25r / min, raise the top bolt, keep the temperature constant for 60s, and lower the top bolt; raise the temperature to 130-146℃, open the discharge door to discharge the compound, and obtain the second-stage compound. (3) Final Refinement Raise the top bolt, adjust the rotation speed to 25-35 r / min, add vulcanizing agent and accelerator to the two-stage compound obtained in step (2), lower the top bolt, and react for 30 seconds; adjust the rotation speed to 20-30 r / min, raise the top bolt, clean, and lower the top bolt; raise the temperature to 100-110℃, open the discharge door to discharge the rubber, and obtain the final compound; (4) Refining The final rubber obtained in step (3) is subjected to open milling at 95-105℃, and the thickness of the rubber sheet is set to 2-3mm. The rubber sheet is then passed through a mill and formed into a triangular shape. This process is repeated 8-12 times. Finally, the sheet is extruded to obtain the tread rubber composition.

8. The application of the tread rubber composition prepared by the method described in claim 7 in tire production.